Cellular origin and diagnostic significance of high‐fluorescent cells in cerebrospinal fluid detected by the XE‐5000 hematology analyzer. Issue 6 (3rd April 2013) - Zimmermann, M.; Otto, C.; Gonzalez, J.‐B.; Prokop, S.; Ruprecht, K.
Summary Introduction The Sysmex XE‐5000 is a blood and body fluid analyzer able to differentiate cells into polymorphonuclear, mononuclear, and high‐fluorescent cells (HFC). The identity of HFC in cerebrospinal fluid (CSF) has been uncertain; however, compatible with their high nucleic acid content, HFC could represent intrathecal tumor cells. Here, we studied the cellular origin and the diagnostic significance of HFC in CSF. Methods Results of CSF examinations with the XE‐5000 were analyzed in 65 CSF samples with and 126 CSF samples without tumor cells, as defined by manual microscopy of CSF cytospin preparations. Results The XE‐5000 detected HFC in 51 of 65 tumor cell–positive and in 33 of 126 tumor cell–negative CSF samples (sensitivity: 78.5%, specificity: 73.8%, positive likelihood ratio: 3.0, negative likelihood ratio: 0.29). The percentages of HFC and tumor cells in CSF samples correlated (r² = 0.41, P < 0.0001). Tumor cells escaped detection by the XE‐5000 especially in CSF samples with a low percentage of tumor cells. Conclusion While this study identifies tumor cells as the predominant correlate of HFC in CSF, it suggests that measuring HFC is not an appropriate diagnostic test for intrathecal tumor cells. However, if HFC are incidentally detected in CSF, further evaluation by CSF microscopy seems mandatory.